The HST Large Programme on NGC 6752. I. Serendipitous discovery of a dwarf Galaxy in background. (10th January 2019) - Bedin, L R; Salaris, M; Rich, R M; Richer, H; Anderson, J; Bettoni, D; Nardiello, D; Milone, A P; Marino, A F; Libralato, M; Bellini, A; Dieball, A; et al.
ABSTRACT: As part of a large Hubble Space Telescope investigation aiming at reaching the faintest stars in the Galactic globular cluster NGC 6752, an Advanced Camera for Surveys/Wide Field Channel field was the subject of deep optical observations reaching magnitudes as faint as V ∼ 30. In this field, we report the discovery of Bedin I, a dwarf spheroidal galaxy too faint and too close to the core of NGC 6752 for detection in earlier surveys. As it is of broad interest to complete the census of galaxies in the local Universe, in this letter we provide the position of this new object along with preliminary assessments of its main parameters. Assuming the same reddening as for NGC 6752, we estimate a distance modulus of ( m − M )0 = 29.70 ± 0.13 from the observed red giant branch, i.e. 8.7^+0.5_-0.7 Mpc, and size of ∼840 × 340 pc, about one-fifth the size of the Large Magellanic Cloud. A comparison of the observed colour–magnitude diagram with synthetic counterparts, which account for the galaxy distance modulus, reddening, and photometric errors, suggests the presence of an old (∼13 Gyr) and metal-poor ([Fe/H] ∼ −1.3) population. This object is most likely a relatively isolated satellite dwarf spheroidal galaxy of the nearby great spiral NGC 6744, or potentially the most distant isolated dwarf spheroidal known with a secure distance.